P561 Developing surveillance tools to measure MSM's HIV infection risk in the era of complex biobehavioural prevention strategies. (14th July 2019) - Frankis, Jamie; Flowers, Paul; Wallace, Lesley; Goldberg, David; Holt, Martin; Mcdaid, Lisa
Abstract : Background: Behavioural surveillance enables monitoring of disease epidemics, assessment of health promotion, development of health policy and service planning. However, the emergence of multiple effective biobehavioral risk management strategies to prevent HIV transmission (including PrEP, treatment-as-prevention (TasP), negotiated safety (NS), serosorting, condom use), demands new surveillance tools able to reflect this complexity. Here, we critically discuss our new surveillance tool, developed to measure MSM's biobehavioural HIV risk-taking. Methods: Items were developed with surveillance experts in Scotland and Australia, piloted within Scotland, then delivered within the Scottish Gay Men's Bar Survey (n=972 MSM), across the commercial gay scenes of Scotland's two largest cities in 2017. Participants were asked about sex with regular and casual partners separately, condom use and condomless anal intercourse (CAI), their HIV status, PrEP use and their partners' HIV and undetectable viral load (UVL) status. Results: Overall, 5.6% of participants were HIV+. For our HIV-/untested participants, 67.7% were categorised as 'lower risk' since, in the last year, they reported; (i) PrEP use (4.5%) (ii) no CAI (37.1%) (iii) Negotiated safety; CAI with 1 regular HIV- partner (16%) (iv) TasP; CAI with 1 regular HIV+ UVL partner (0.4%) (v) Serosorting; CAI with casual and/or multiple regular HIV- partners (4.1%) (vi) Both serosorting and TasP CAI with multiple regular and casual partners (5.4%) The remaining 32.3% were categorised as 'higher risk'; HIV-/untested men not on PrEP who reported CAI with HIV status-unknown partners, or HIV+ partners with unknown/detectable viral load. Of these, 67.6% report 2+ CAI partners, making them potentially eligible for PrEP in Scotland. Conclusion: No CAI, NS and PrEP were the key biobehavioural risk strategies used. Two-thirds of our higher risk men could, but are yet to, benefit from PrEP. Although offering new insights, we invite critical engagement with these risk criteria which present different, yet related challenges for researchers and MSM alike. Disclosure: No significant relationships.